Price stability and climate risks: Sensible measures for the European Central Bank - Franziska Bremus; Geraldine Dany-Knedlik; Thore Schlaak (DIW Weekly Report, 2020)
By the end of 2020, the European Central Bank (ECB) will present the results of its monetary policy strategy review. What changes are to be expected and what changes are needed? This report covers two areas of the strategy review. First, alternatives to the current definition of price stability are discussed. Current studies and the practices of other central banks indicate that supplementing the inflation target with a tolerance interval may be useful to enhance central bank credibility. Second, it is discussed to what extent climate risks play a role in the ECB's economic analyses and monetary policy measures. Empirical evidence shows that weather events such as extreme droughts or floods can influence business cycles in the euro area. Overall, climate risks should be assessed both as part of the ECB's macroeconomic and monetary analyses and as part of its portfolio and risk management.
Keywords: E31; E32; E52; E58; 330; monetary policy; price stability; climate risks